Engineering and Economic Evaluation of Production of Fe3O4 Nanoparticles - Asha E. Harman; Asep Bayu Dani Nandiyanto (Politeknik Negeri Malang, 2020)
This paper aims to evaluate the economic feasibility of Fe 3 O 4 nanoparticle production from a laboratory scale to an industrial scale feasibility. The evaluation was conducted using 2 models of feasibility studies, namely: technical analysis and economic evaluation. Technical analysis provides information on the potential for large-scale production and the results of this process can be applied using commercially available and inexpensive equipment. Economic evaluation is based on a comparison of the Cumulative Net Present Value graph in an ideal condition and the graph when parameters changing are made (such as changes in the dollar exchange rate, the quantity of sales products, and the value of employee salaries). From the evaluation results, all parameter changes give a positive value indicating that the project is feasible to run commercially and on a large scale. This is because the evaluation results provide a stable index of profit for some changes in parameter values. This study shows that Fe 3 O 4 fabrication can provide promising profits in developing countries and can attract foreign investors to work together on Fe 3 O 4 fabrication.